Gambaran Kecerdasan Emosional Mahasiswa Prodi D-III Kebidanan dan Program Studi Sarjana Terapan Berlanjut Pendidikan Profesi Bidan - Triwik Sri Mulati (Jurnal Kebidanan dan Kesehatan Tradisional, 2020)
Background: Psychological theory reveals that emotional intelligence influences human behavior. One of them is student behavior in the learning process will be influenced by the emotional intelligence he has. With good emotional intelligence, students tend to be more responsible in carrying out their roles as students. But in fact, not many teaching staff at the Educational Institution pay attention to the teori about the importance of emotional intelligence, whereas if emotional intelligence is developed in an educational institution it will optimize student responsibility, behavior and learning achievement. Aims study to describe the emotional intelligence of students of the Department of Midwifery Diploma Program and Continued Applied Bachelor Study Program Professional Education Midwife Professional Program in the Midwifery Department of the Polytechnic of the Ministry of Health Surakarta. The results of this study are expected to be used as an additional reference and input to teaching staff, especially in the Surakarta Health Polytechnic and Education Institutions in general to develop emotional intelligence in order to increase student responsibility, behavior and learning achievement. Methods: This type of research is descriptive. Univariate data analysis uses frequency distribution. Results: The level of emotional intelligence in midwifery DIII program is quite good 98.8% and good 1.2%. The level of emotional intelligence in midwifery applied bachelor is quite good 52.7%, good 44.9%, and very good 2.7%. Conclusion: Most midwifery students have good emotional intelligence.